Reformulation of Legal Norms Regarding the Spread of Criminal Radicalism Through Social Media in Indonesia - Nugroho Marsudianto, Dwi; Santiago, Faisal (Green Publisher Indonesia, 2024)
The spread of radical ideology through social media has become a serious challenge that requires more effective legal attention and action. This research proposes the need for a revision of existing regulations, particularly in defining radicalism and establishing strict actions as radical offenses, as well as the formation of implementing regulations that support the monitoring of harmful content. Furthermore, the importance of social media platforms' responsibility in managing radical content is outlined as part of the cooperation between the government, digital service providers, and society. This research also emphasizes the need for a comprehensive implementation strategy and the active role of law enforcement agencies to ensure effective law enforcement, aimed at creating a safer environment free from the influences of radicalism.